83 10-YEAR CHANGES IN DIETARY HABITS AND MEDICAL KNOWLEDGE OF ESOPHAGEAL CANCER IN A HIGH-INCIDENCE AREA: A POPULATION-BASED STUDY. (14th September 2020) - Tian, D; Huang, H; Jiang, K; Wen, H; Fu, M
Abstract: : Yanting was reported as a high-incidence area of EC with an unclear etiology. Many preventative measures and control policies have been performed during recent years in Yanting County, but no study has examined the changes in dietary habits and medical knowledge of EC during this decade. This study aimed to compare the differences in dietary habits, food group intake and medical knowledge of EC among residents of Yanting between 2007 and 2017. Methods: Using a self-designed questionnaire, we investigated rural residents from Yanting county in the year 2007 and 2017. The 10-year changes of demographic features, personal dietary habits, food groups and medical knowledge of EC were compared. The results were then statistically analyzed. This study is based on a household survey of 570 and 898 rural residents aged 18+ years from Yanting County conducted in 2007 and 2017, respectively. Results: Participants in the year 2007 were more likely to consume foods of lower toughness, have a slower speed of eating, have hotter temperature food, and have rice as a staple food less often (P < 0.05). Residents in the year 2007 ate more preserved foods but fewer fresh foods than those in the year 2017 (P < 0.05). Participants in the year 2017 improved their medical knowledge compared to those in the year 2007, which was conceptualized as a clear understanding of medical insurance for EC, common causes of EC, therapeutic measures for EC, preventive measures for EC, and government interventions (P < 0.05). Conclusion: Although the medical knowledge of participants in year 2017 have changed a lot, most of them also never head of detail knowledge on EC. Residents in the year 2017 had healthier dietary habits and better medical knowledge of EC than those in the year 2007, while prevention and control measures in Yanting should be strengthened persistently.